Preferensi Konsumen berdasarkan Usia, Pendidikan dan Jenis Kelamin terhadap Kopi Aren Rasa Wine Non Alkohol di Coffee Shop Jabu Hela Medan - Mirza, Deni Faisal; Shella, Shella; Mirza, M.Fadhlan (Journal of Management and Bussines (JOMB), 2024)
This study aims to determine the effect of age, education, gender on the interest in drinking non-alcoholic wine flavoured Aren Coffee at Jabu Hela Coffee Shop Medan, both together and individually. A quantitative approach was used in compiling this research. Data analysis was arranged with multiple linear analysis. The research shows the results partially from the influence of age, education, gender, influence the interest in drinking nonalcoholic wine flavoured palm coffee at Coffee Shop Jabu Hela Medan. Simultaneously there is an influence of age, education, gender on the interest in drinking nonalcoholic wine-flavoured palm coffee at Coffee Shop Jabu Hela Medan. The value of determination in the coefficient obtained is 0.371 which means that Age, Education, Gender on Interest in Drinking Nonalcoholic Wine Flavoured Aren Coffee at Coffee Shop Jabu Hela Medan is 37.1% and the remaining 62.9% is explained by other variables that are not analysed outside of this study. Keywords : Age, Education, Gender, Interests